2019
DOI: 10.1093/rap/rkz020
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in people with rheumatic disease in Finland 1995–2007: a nationwide retrospective register study

Abstract: Objectives RA and its medication, especially TNF-α inhibitors, increase the risk of clinical tuberculosis (TB) infection. We aimed to investigate the clinical manifestations, incidence and temporal changes in TB occurring concurrently with rheumatic diseases (RDs) between 1995 and 2007. Methods We combined the register of the Social Insurance Institution of Finland and the National Infectious Disease Register to find adult pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
1
8
0
2
Order By: Relevance
“…In a nationwide retrospective register study performed in Finland, it was noted that between 1995 and 2007 the incidence of TB in adult RD patients with reimbursed DMARDs decreased from 58.8 to 30.0 per 100,000. This trend was similar to that in the general population and was explained by an improved standard of living and by strict TB control during the 20th century [13].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In a nationwide retrospective register study performed in Finland, it was noted that between 1995 and 2007 the incidence of TB in adult RD patients with reimbursed DMARDs decreased from 58.8 to 30.0 per 100,000. This trend was similar to that in the general population and was explained by an improved standard of living and by strict TB control during the 20th century [13].…”
Section: Discussionsupporting
confidence: 77%
“…This risk is probably associated with immunosuppression linked to the disease and the use of other medications such as corticosteroids [4,6,7,12]. Studies from Sweden and Finland (countries with a low incidence of TB) found that compared with the general population, even rheumatic patients not treated with biologicals had a fourfold increased risk of TB [6,13]. Studies suggest that the incidence of development of TB should be even more considerable in patients who live in countries with a high incidence of this infection in the general population [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the number of patients with extrapulmonary TB was 8 (15.7%), which seems to be numerically similar to the proportion of extrapulmonary TB arising in immunocompetent subjects and is contradictory to the knowledge that patients under TNF-α inhibitors are more prone to extrapulmonary TB (40). In addition, even though the number of incident TB cases were not large, a recent publication by Chung et al reported that a proportion of extrapulmonary TB in patients with rheumatoid arthritis (RA) was 38.5% (41), and a study by Vuorela et al has shown that ∼23.9% of patients with rheumatic diseases are affected with extrapulmonary TB (42). Several factors could be accounted for the discrepant results between the previous studies and our study.…”
Section: Discussionmentioning
confidence: 96%
“…In 2016, 6.3 million new cases of TB and 1.3 million cases of TB-related death were reported among human immunodeficiency virus (HIV)-negative patients [ 1 ]. Although its incidence has been slowly decreasing since 2002, it is still a significant co-morbidity in patients with rheumatic diseases because the immunosuppressive agents used to treat rheumatic diseases increase the risk of TB [ 2 ]. Among the various immunosuppressive agents, high-dose glucocorticoids, a mainstay of the treatment of many rheumatic diseases, are particularly known to increase the TB risk [ 3 ].…”
Section: Introductionmentioning
confidence: 99%